The effect of hypoxia on Daphnia magna performance and its associated microbial and bacterioplankton community: A scope for phenotypic plasticity and microbiome community interactions upon environmental stress? - Coone, Manon; Vanoverberghe, Isabel; Houwenhuyse, Shira; Verslype, Chris; Decaestecker, Ellen (Frontiers in Ecology and Evolution, 2023)
The depletion of oxygen as a result of increased stratification and decreased oxygen solubility is one of the most significant chemical changes occurring in aquatic ecosystems as a result of global environmental change. Hence, more aquatic organisms will be exposed to hypoxic conditions over time. Deciphering the effects of hypoxia on strong ecological interactors in this ecosystem’s food web is critical for predicting how aquatic communities can respond to such an environmental disturbance. Here, (sub-)lethal effects of hypoxia and whether these are genotype specific in Daphnia, a keystone species of freshwater ecosystems, are studied. This is especially relevant upon studying genetic responses with respect to phenotypic switches upon environmental stress. Further, we investigated the effect of hypoxia on the Daphnia microbial community to test if the microbiome plays a role in the phenotypic switch and tolerance to hypoxia. For this, two Daphnia genotypes were exposed for two weeks to either hypoxia or normoxia and host performance was monitored together with changes in the host associated and free-living microbial community after this period. We found phenotypical plastic responses for some of the tested Daphnia performance traits. The microbial community of the bacterioplankton and Daphnia associated microbial community responded via changes in species richness and community composition and structure. The latter response was different for the two genotypes suggesting that the microbiome plays an important role in phenotypic plasticity with respect to hypoxia tolerance in Daphnia, but further testing (e.g. through microbiome transplants) is needed to confirm this.